The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/lary.25187
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the cochlear implant experience in children with enlarged vestibular aqueduct

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Whether there is a difference in audiometric outcomes between these IEVA and IP-II malformations is unclear at present. This aspect was also studied in a retrospective study of 55 patients who had cochlear implantation (IEVA ¼ 18, IP-II ¼ 33, IP-I ¼ 3) (17). Mean age at implantation for IEVA group was 112.8 months which was significantly different from IP-II group (58.4 mo).…”
Section: Discussionmentioning
confidence: 99%
“…Whether there is a difference in audiometric outcomes between these IEVA and IP-II malformations is unclear at present. This aspect was also studied in a retrospective study of 55 patients who had cochlear implantation (IEVA ¼ 18, IP-II ¼ 33, IP-I ¼ 3) (17). Mean age at implantation for IEVA group was 112.8 months which was significantly different from IP-II group (58.4 mo).…”
Section: Discussionmentioning
confidence: 99%
“…An examination of the literature studies revealed that the hearing loss associated with IP-II and LVA malformations is heterogeneous, and the conductive component is not associated with middle ear pathologies [2,12,13,17,18,[20][21][22][23][24][25][26] . Roesch et al [25] found that patients with IP-II and isolated LVA malformations were diagnosed not only with severe to profound hearing loss but also with moderate asymmetrical hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been many reports on the outcome of CI in patients with EVA, most of them focused on children and did not include the results of genetic analysis. 5,6,8,9,14,15) There are few reports on the outcome of CI performed in the adult period in patients with EVA. Miyamoto, et al 7) reported the outcome of CI in 14 adults and 9 children with EVA, and concluded that the auditory and speech recognition performance did not differ compared to control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that children with isolated EVA demonstrated better speech performance following CI compared to those with concomitant cochlear anomalies, although statistical significance was not reached. 9) When managing hearing loss in patients with EVA, special patient characteristics have to be considered. There is a wide variability concerning the degree of residual hearing in the prelingual period that either progress gradually or suddenly aggravate in the adolescent or adult period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation